Integrated disaster management and smart insurance using cloud and internet of things - Koduru, Suresh; Reddy PVGD, Prasad; Padala, Preethi (International Journal of Engineering and Technology, 2018)
Over a period of decades there are lot of frequent disruptions due to natural, man-made and technological disasters which are seriously effecting the society, environment and economy. Hence it is vital that an effective integrated disaster management must be defined by integrating various types of disasters for being equipped in real time to face disasters in an extremely short span of time. In this paper a framework for disaster management is defined based on cloud and internet of things. A disaster management use case is developed based on the defined framework by integrating natural and manmade disasters. Natural disaster events are integrated to derive the probable insurance claims based on historical data and for the insurance agencies to be equipped in the event of disaster. Manmade disaster events will alert the end users when disaster events are about to occur. Here heterogeneous devices and data are firmly integrated to monitor various disaster events at one stop.Â